ATIM-24. DOSE FINDING AND DOSE EXPANSION TRIAL OF D2C7 IMMUNOTOXIN (D2C7-IT) ADMINISTERED INTRATUMORALLY VIA CONVECTION-ENHANCED DELIVERY (CED) FOR RECURRENT MALIGNANT GLIOMA (MG). (11th November 2019) - Desjardins, Annick; Randazzo, Dina; Chandramohan, Vidya; Peters, Katherine; Johnson, Margaret; Threatt, Stevie; Bullock, Chevelle; Jackman, Jenny; Healy, Patrick; Lipp, Eric; Sampson, John; Friedman, Allan; et al.
Abstract: BACKGROUND: D2C7-IT is a recombinant immunotoxin comprised of a dual-specific antibody fragment targeting EGFRwt and EGFRvIII and a genetically engineered form of the Pseudomonas exotoxin, PE38-KDEL. We report results of a phase 1 trial, with dose expansion at the selected phase 2 dose, evaluating D2C7-IT delivered intratumorally by CED. METHODS: Eligible patients are adults with recurrent supratentorial WHO grade III or IV MG; solitary tumor; ≥4 weeks after chemotherapy, bevacizumab or study drug; adequate organ function; and KPS >70%. Two patients per dose level (DL) were to be enrolled in the dose escalation portion (dose range: 40ng/mL to 23, 354ng/mL), followed by dose expansion at the selected phase 2 dose (DL13). RESULTS: As of 6/07/2019, 51 patients have been treated; 10 patients on the phase 2 dose. Observed dose limiting toxicities include: grade 4 seizure (n=1) on DL3, grade 3 confusion and pyramidal tract syndrome (n=1) on DL13, and grade 4 cerebral edema (n=1) and grade 3 dysphasia (n=1) on DL17. Grade 3 or higher adverse events possibly related to D2C7-IT include: seizure (grade 4, n=2, grade 3, n=3), cerebral edema (grade 4, n=1), hydrocephalus (grade 3, n=5), headache (grade 3, n=4), hemiparesis (grade 3, n=4), dysphasia (grade 3, n=4), lymphopenia (grade 3, n=3), thromboembolic event (grade 3, n=3); and one each of grade 3 elevated ALT, urinary tract infection, fall, wound complication, generalized muscle weakness, confusion, encephalopathy, and somnolence. Fourteen patients are alive. Three patients have partial radiographic response and remain alive without additional therapy more than 46, 27 and 21 months after D2C7-IT infusion. CONCLUSION: Dose level 13 was selected as the optimal phase 2 dose and patient accrual is ongoing on the dose expansion arm. Encouraging efficacy results have been observed. A trial of D2C7-IT with checkpoint inhibitor is planned to start in the near future.